Using Supervised Classification to Detect Political Tweets with Political Content - Amorim, Brunna de Sousa Pereira; Alves, André Luiz Firmino; de Oliveira, Maxwell Guimarães; Baptista, Cláudio de Souza (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2018)
Social media platforms have been increasingly used by modern society. In most platforms, users usually share content on various subjects and, in particular, politics is a favorite one. There are many interests in detecting and analyzing such a political content. However, there is a challenge in the process of detecting specific subjects from social media data mainly due to its informality. In this paper, we propose and compare two techniques, based on supervised classification, for the detection of tweets with political content. The results obtained by our approach have demonstrated satisfactory performance, which motivates further research to be undertaken.